2010
DOI: 10.1007/s11547-010-0536-x
|View full text |Cite
|
Sign up to set email alerts
|

Density-based MDCT quantification of lobar lung volumes: a study of inter- and intraobserver reproducibility

Abstract: MDCT quantification of total and emphysematous lung volume and emphysema index is overall reproducible. Quantitative assessment of those parameters performed on single lobes is affected by variability. An improvement of the reproducibility of q-MDCT is expected from the use of advanced methods for lobar segmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…A trend of high variability was also noted for the right middle lobe in the interoperator analysis. As reported previously, the smaller absolute volume of the right middle lobe leads to considerable relative differences, which are also expected because the minor fissure is typically less pronounced and therefore more difficult to delineate (10).…”
Section: Coefficient Of Reproducibility (Ml)supporting
confidence: 68%
See 3 more Smart Citations
“…A trend of high variability was also noted for the right middle lobe in the interoperator analysis. As reported previously, the smaller absolute volume of the right middle lobe leads to considerable relative differences, which are also expected because the minor fissure is typically less pronounced and therefore more difficult to delineate (10).…”
Section: Coefficient Of Reproducibility (Ml)supporting
confidence: 68%
“…Quantitative CT techniques for emphysema scoring are objective and therefore preferable to visual analysis (7). Recent studies have also demonstrated that CT lobar volumetry has good inter scan reproducibility (8)(9)(10). Among the different sources of variability of CT lung volumetry and emphysema scoring, those depending on the method used for lobar segmentation have received little attention (5).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Lobe-specific measurements may provide insight into both underlying disease mechanisms and the spectrum of disease phenotypes (particularly in chronic obstructive lung disease), as well as help to refine therapeutic strategies (4)(5)(6). Prior studies also evaluated the reliability of the corresponding measurements by testing the inherent interoperator variability or comparing software results with the visual score (7,8). However, the accuracies of CT-based lobe segmentation and measurements have yet to be proven in comparison with a gold standard, such as pathological measurements.…”
mentioning
confidence: 99%